2011
DOI: 10.1002/chem.201100929
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantio‐ and Diastereoselective Synthesis of β‐Methyl‐γ‐monofluoromethyl‐Substituted Alcohols

Abstract: Enanatiopure β-methyl-γ-monofluoromethyl alcohols were prepared from the allylic alkylation between fluorobis(phenylsulfonyl)methane with Morita-Baylis-Hillman carbonates. The reaction was catalyzed by using the Cinchona alkaloid derivative, (DHQD)(2)AQN. The origin of the stereoselectivity was verified by DFT methods. Calculated geometries and relative energies of various transition states strongly support the observed stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 98 publications
1
20
0
1
Order By: Relevance
“…This could be explained by bidentate chelation [17] of FBSM with the Lewis acid, thus locking the FBSM conformation so as to favor a closed conformation (III; Scheme 6 c), although the closed conformation is an inherent preference of a FBSM carbanion even in the absence of Lewis acid. [19] A 1 H NMR investigation of 1:1 mixture of FBSM and Ti(OiPr) 4 in [D 6 ]benzene strongly supports this hypothesis, since the methine proton of FBSM gives a signal that is d = 0.036 ppm downfield relative to the signal in the original spectrum of FBSM (see Figure S2 and S3 in the Supporting Information). In the locked closed conformation III, FBSM would easily approach the reaction center and avoid steric interactions in the transition state I, although this outcome is dependent on the substate structure (Scheme 6 a).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This could be explained by bidentate chelation [17] of FBSM with the Lewis acid, thus locking the FBSM conformation so as to favor a closed conformation (III; Scheme 6 c), although the closed conformation is an inherent preference of a FBSM carbanion even in the absence of Lewis acid. [19] A 1 H NMR investigation of 1:1 mixture of FBSM and Ti(OiPr) 4 in [D 6 ]benzene strongly supports this hypothesis, since the methine proton of FBSM gives a signal that is d = 0.036 ppm downfield relative to the signal in the original spectrum of FBSM (see Figure S2 and S3 in the Supporting Information). In the locked closed conformation III, FBSM would easily approach the reaction center and avoid steric interactions in the transition state I, although this outcome is dependent on the substate structure (Scheme 6 a).…”
mentioning
confidence: 82%
“…In the locked closed conformation III, FBSM would easily approach the reaction center and avoid steric interactions in the transition state I, although this outcome is dependent on the substate structure (Scheme 6 a). [19,20] In summary, the organocatalyzed enantioselective allylic monofluoromethylation of Morita-Baylis-Hillman carbonates using FBSM was achieved in high yields with high ee values for the first time. [19b] Cooperative catalysis with bis(cinchona alkaloid) and FeCl 2 was found to be most suitable for this transformation.…”
mentioning
confidence: 99%
“…demonstrated that the resulting adducts 43 could be transformed into g-(fluoromethyl)alcohols sucha s44 by hydrogenation, which was completely diastereoselective, followed by reduction of the ester and reductive cleavage of the sulfones with magnesium and iodine. [21] In addition to their utility for allylic alkylations, fluorinated bis(sulfones) are also good nucleophilesf or 1,2-additions to carbonyl compounds. Shibata showed that N-Boc aldimines 47,g enerated in situ from a-aminosulfones 45,c ould be intercepted by 30 under asymmetric phase-transfer catalysis.…”
Section: Fluoromethyl Anionmentioning
confidence: 99%
“…Good to very good results were observed utilizing (DHQD) 2 AQN 119 again. [124] Additionally the group reported successful reactions with other sulfonyl nucleophiles [125] and with a,a-dicyanoalkenes. [126] Trifluoromethylation reactions of MBH carbonates were reported by Shibata et al also applying a bis-cinchona catalyst 121.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%